Tatars in the Grand Duchy of Lithuania in the 14th–16th Centuries - Pylypchuk, Yaroslav (Lietuvos istorijos studijos, 2023)
This article is dedicated to the history of the Tatars in the Grand Duchy of Lithuania. Tatars in the Grand Duchy of Lithuania played an important role in border guarding. They carried out border, ambassadorial and castle service. Interpreters of Tatars and Tatar beks were sent on important missions to estab- lish diplomatic relations with strong Turkic states. Apostates (apostates from Is- lam) Glinskie played an important role in protecting the Ukrainian border from Crimean raids. Representatives of this family went on diplomatic missions to the Big Horde. The rulers of the Great Horde and the Crimean Khanate did not con- sider it shameful to write to the apostate and the provincial prince. The Tatar origin of the clan, on the contrary, was a plus in the eyes of the Jochids and the Glinskie were generally perceived as their own people. The adoption of Christian- ity opened up broad career prospects. Tatars managed to preserve their identity in places of compact settlement of Tatars in Belarus and Lithuania, as well as in Volyn. However, many Tatars who received land in the Grand Duchy of Lithuania quickly lost their ethnic and religious identity.
Keywords: Grand Duchy of Lithuania; Tatars; Glinskie; apostates; Volhynia; Jochids